2010
DOI: 10.7150/ijbs.6.827
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Microsatellite DNA Markers Reveals no Genetic Differentiation between Wild and Hatchery Populations of Pacific Threadfin in Hawaii

Abstract: Pacific threadfin, Polydactylus sexfilis, is popular fish in recreational fishing, as well as aquaculture in Hawaii. Its natural population has been continuously declining in the past several decades. Microsatellite DNA markers are useful DNA-based tool for monitoring Pacific threadfin populations. In this study, fifteen Microsatellite (MS) DNA markers were identified from a partial genomic Pacific threadfin DNA library enriched in CA repeats, and six highly-polymorphic microsatellite loci were employed to ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Briefly, tissue samples were digested with 0.5 g/l proteinase K at 55°C overnight. The resulting solution was centrifuged; the supernatant was extracted by phenol-chloroform and precipitated in ethanol and dissolved in 1X TE buffer [15]. The quality and concentration of DNA were assessed by spectrophotometer and agarose gel electrophoresis, and DNA samples were stored at 4°C until use.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, tissue samples were digested with 0.5 g/l proteinase K at 55°C overnight. The resulting solution was centrifuged; the supernatant was extracted by phenol-chloroform and precipitated in ethanol and dissolved in 1X TE buffer [15]. The quality and concentration of DNA were assessed by spectrophotometer and agarose gel electrophoresis, and DNA samples were stored at 4°C until use.…”
Section: Methodsmentioning
confidence: 99%
“…Such adverse genetic effects on natural population restoration have been previously reported by Araki et al 2007;Cheng et al 2011 andLi et al 2016. Nevertheless, there have also been reports on maintaining genetic variability in hatchery populations of other fish species (Pan and Yang 2010;.…”
Section: Introductionmentioning
confidence: 68%
“…Similar to the present study, a low level of population differentiation (FST)was also observed among populations and significant differentiation (P<0.05) was evident only between the Halda riverine and hatchery populations in Bangladesh in Catla catla . Another recent study found that there is no genetic differentiation (FST = 0.001) between wild and hatchery population of Paciifc threadfin in Hawaii (Pan & Yang, 2010). Homogeneity tests for pair-wise comparisons of different stocks showed that the HatcheryHatchery♂ × Padma♀ populations are more homogeneous compared to the Padma-Hatchery♂ × Padma♀ and Padma-Hatchery population pairs (Table 5).…”
Section: Discussionmentioning
confidence: 99%